The Evolution of Organ Shape : Distal Tip Cell Migration and Gonadogenesis in Nematodes - Wyatt, Brent (East Carolina University, 2013)
Animals display a variety of shapes in nature. The different shape of homologous organs allows them to adopt different functions and therefore, allows animals to live in different ecological niches. However, little is understood about the cellular and molecular mechanisms involved in the evolution and development of organ morphology. We compare gonad development in two closely related nematode species, Pristionchus pacificus and Caenorhabditis elegans to address how a tube can change shape. The hermaphrodite gonad in each of these species consists of two tube-shaped rotationally symmetrical gonadal arms. There is a novel ventral migration observed in P. pacificus that is not observed in C. elegans. Extension of the gonadal arms in both of these species is lead by the distal tip cell (DTC), which is a single cell that caps the end of the extending arm. Previous studies have shown that the DTCs in P. pacificus receive a signal from the vulva to extend ventrally during development. However, it is not clear how the DTCs are responding to dorsal/ventral positional information to accomplish this novel migration. Here, we show early data that the Netrin cell guidance cue may be involved in dorsal/ventral migrations of the P. pacificus DTC. Specifically, we show Ppa-unc-40/Netrin receptor may be a major player in dorsal/ventral migrations of the DTC.
Keywords: Biology; Distal tip cell; Gonadogenesis; C. elegans; Caenorhabditis elegans; Diplogasterida; Evolution (Biology)